Adaptasi Perilaku Kepedulian Lingkungan Anak SD melalui Konsep Cerita Animasi Memayu Hayuning Bawana - Nimas Fadhilatur Rohmah; Diana Aqidatun Nisa; Restu Ismoyo Aji (JPKS (Jurnal Pendidikan dan Kajian Seni), 2026)
This study aims to analyze and adapt environmental care behaviors of first-grade elementary school students through the values of Memayu Hayuning Bawana within a narrative animation concept. This Javanese philosophical framework emphasizes harmony through balanced relationships between humans, nature, and spiritual awareness. The study employed a qualitative approach with a descriptive-interpretative method. Data were collected through observations of students’ behavior and interviews with a first-grade teacher at SDN Bareng 2 Jombang, supported by a literature review. Data analysis involved reduction, categorization, and interpretation by linking empirical findings with the core values of Memayu Hayuning Bawana. The results indicate that students have demonstrated environmental care behaviors, such as maintaining cleanliness, participating in collaborative activities, and following environmental rules. However, these behaviors remain at the habituation stage and have not yet developed into independent awareness. These findings are interpreted through the values of eling lan waspada, karyenak tyasing sesama, sepi ing pamrih rame ing gawe, tepo seliro and bisa rumangsa. Based on the synthesis of empirical data and theoretical analysis, this study formulates adaptive behavioral practices and translates them into a narrative animation concept that represents everyday school situations. Each value is embodied through simple conflicts and resolutions to support children’s understanding of environmental care behavior. The findings suggest that Memayu Hayuning Bawana serves as both a conceptual and practical foundation for culturally-based environmental education, particularly when integrated into visual storytelling approaches that are contextual, engaging, and developmentally appropriate for early primary school children.